Estimated dietary intake and risk assessment of polychlorinated dibenzo-p-dioxins and dibenzofurans and dioxin-like polychlorinated biphenyls from fish consumption in the Korean general population - Shin, ES; Kim, J; Choi, SD; Kang, YW; Chang, YS (Chemosphere, 2016)
We analyzed 17 polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), and 12 dioxin-like polychlorinated biphenyls (DL-PCBs) in samples from various fish species available at food markets in nine Korean cities. The estimated dietary intake of these chemicals was calculated from the raw concentrations of PCDD/Fs and DL-PCBs in each sample and from the food consumption of the Korean general population, and a comparison was made with the provisional tolerable monthly intake (PTMI). The average daily dietary exposure and the 95th percentile of intake of PCDD/Fs and DL-PCBs were 0.21 and 0.49 pg WHO05-toxic equivalents (TEQ) kg(-1) body weight d(-1) representing 5.27% and 12.26%, respectively, of the Korean tolerable daily intake (TDI). We applied the monthly fish consumption limits to the evaluation of improved risk assessment and concluded that unlimited consumption of most fish species does not contribute to the elevated cancer risk. This investigation was the first such large-scale study in Korea, and incorporated 37 species, including a species of whale, and 480 samples. The major aims of this study were to demonstrate the health risks associated with fish intake and to ensure food safety through total analysis of PCDD/Fs and DL-PCBs using gas chromatography/high-resolution mass spectrometry (GC-HRMS). (C) 2015 Elsevier Ltd. All rights reserved. 1 1 10 N scie scopus